ANALISA KERETAKAN PADA KONSTRUKSI GELADAK UTAMA KM. ADRI XLIV - Djazuli Sa’id, Solichin (Gema Teknologi, 2012)
Solichin Djazuli Sa’id, in this paper explain that ship KM. XLIV Adri is the kind of cargo ship (General Cargo). The ship has been designed in accordance with the rules and regulations of the class (Bureau of Classification Indonesia). From the results of the survey method of research vessel, discovered the damage to construction on the main deck, the cracks on the fulcrum side deck fit the front room and deck beams are broken the back of the main deck. Thus causing the curvature of the floor deck and it needs to be a replacement / repair of components damaged by construction ensuring shipping safety. From the calculation results and field studies, construction damage caused by welding is not good, cutting the material that is not true and the use of payload on the main deck in excess of the permitted capacity. Key words: Cargo Ship , Construction Damages, Main Deck